COVID-19 : EFEKTIVITAS DAN KEMANAN VAKSIN - Gede Sukma Setiawan (Jurnal Medika Hutama, 2022)
Abstract Various strategies and development of COVID-19 vaccines have been carried out to control the COVID-19 pandemic. Various vaccines have undergone clinical trials with promising results in various countries. The effectiveness and safety as well as short-term and long-term side effects of vaccines are major concerns in clinical trials in these strategies and developments. The purpose of this study is to determine the effectiveness and safety of the COVID-19 vaccine so that it can provide information and increase public confidence in the COVID-19 vaccine through a reference study approach. Methods: The research method we use here is a reference study using an electronic database through international and national journals. Google Scholar, science direx, elsiver, Pubmed were used as the main Journal database for this reference study. In the research process, 35 articles were found but only 28 articles were selected from 2020 to 2021. The result of this article is to explain the latest updates regarding the effectiveness and safety of the COVID-19 vaccine. Keywords: Effectiveness; Security; Vaccine; COVID-19